Phosphorylated neurofilament heavy chain: A biomarker of survival for C9ORF72‐associated amyotrophic lateral sclerosis. Issue 1 (25th July 2017) - Gendron, Tania F.; Daughrity, Lillian M.; Heckman, Michael G.; Diehl, Nancy N.; Wuu, Joanne; Miller, Timothy M.; Pastor, Pau; Trojanowski, John Q.; Grossman, Murray; Berry, James D.; Hu, William T.; Ratti, Antonia; et al.
Abstract : As potential treatments for C9ORF72 ‐associated amyotrophic lateral sclerosis (c9ALS) approach clinical trials, the identification of prognostic biomarkers for c9ALS becomes a priority. We show that levels of phosphorylated neurofilament heavy chain (pNFH) in cerebrospinal fluid (CSF) predict disease status and survival in c9ALS patients, and are largely stable over time. Moreover, c9ALS patients exhibit higher pNFH levels, more rapid disease progression, and shorter survival after disease onset than ALS patients without C9ORF72 expansions. These data support the use of CSF pNFH as a prognostic biomarker for clinical trials, which will increase the likelihood of successfully developing a treatment for c9ALS. Ann Neurol 2017;82:139–146